(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Inadequate nutrition in the first five years of life results in irreversible physical and mental growth and developmental disorders. According to the results of Basic Health Research or Riskesdas (2018) mention that Malnutrition are 17.7% in Indonesia consist of 3.9% toddlers with malnutrition 13.8% high malnutrition. To reduce the number is with PMT. The purpose of this study is to get a detailed picture of the implementation of the PMT nutrition program. Research methods, research design tativoe. The research phase begins with data collection, data reduction, data presentation, and drawing conclusions and verification. The number of informants involves 13 people. The methods used were FGD and interview. The results of the research, showing the process of preparation, implementation, monitoring and recording during the pandemic remain implemented in accordance with the specified program. Suggestions, increase the role of cadres and community leaders in succeeding PMT programs, especially during the pandemic.